PP.40.19: CHANGES IN PULSE WAVE VELOCITY AFTER INVASIVE TREATMENT OF RESISTANT HYPERTENSION. (June 2015) - Berra, E.; Rabbia, F.; Covella, M.; Testa, E.; Totaro, S.; Fulcheri, C.; Di Monaco, S.; Milan, A.; Pappacogli, M.; Leone, D.; Veglio, F.
Abstract : Objective: renal sympathetic denervation with radiofrequency (RDN) and baroreflex activation therapy (BAT) have been recently developed as invasive options for the treatment of drug-resistant hypertension (RH). The aim of the study was to analyze the presence of a correlation between the change in office blood pressure (officeBP) and 24 hours blood pressure monitoring (ABPM) and modifications in arterial stiffness measured by pulse wave velocity (PWV) in patients with RH who underwent invasive treatment. Design and method: 6 patients underwent RDN and 3 patients BAT; 1 patient was treated with both methods for lack of response to BAT. All patients were receiving at least 5 antihypertensives at full dose and had been followed for at least 6 months in a referral center for high blood pressure. Office BP measurement, ABPM and PWV were performed at baseline and 6 months after RDN/BAT, considering as responders patients with a reduction of the office BP > 10%. Results: Analyzing overall data of 9 patients we observed a 34 mmHg reduction in office BP, a 12 mmHg reduction in 24-hour systolic BP and a 1.15 m/s reduction in PWV. Subsequently, data were analyzed dividing patients into two groups according to the responder status. Six months after the procedure, the 2 responders had a office SBP –reduction of 93 mmHg, ABPM SBP reduction of 59 mmHg and PWV reduction of 0.8 m/s; among the non responders the changes in office SBP, ABPM SBP and PWV were respectively -5 mmHg, +1.5 mmHg and -1.3 m/s. Conclusions: Both in responders and in non responders we observed a trend towards PWV reduction that appears independent of the reduction in BP values.